Enhancing the Growth and Yield of Lembah Palu Shallot Variety (Allium wakegi Araki) Using Azotobacter sp. - Maemunah, Maemunah; Marhani, Marhani; Fadilah D, Fani (Journal of Technology and Engineering, 2025)
Nitrogen is the main component of protein, relatively unavailable to plants even though nitrogen molecules account for 80 percent of the total elements in the atmosphere. Azotobacter bacteria can play a role in increasing soil fertility and are capable of fixing free nitrogen from the air. This study aims to examine the optimal concentration of Azotobacter sp. bacteria for shallot plants of the Lembah Palu variety to support growth and production. This research was conducted at the Agronomy Laboratory and Screen House of the Academic Garden, Faculty of Agriculture, Tadulako University, Palu, from August 2024 to July 2025. The experiment was arranged using a Completely Randomized Design (CRD) consisting of five treatments with three replications. The treatments included control (without Azotobacter sp.), 100 ml Azotobacter sp., 1:5 (17 ml Azotobacter sp. + 83 ml water), 1:10 (9 ml Azotobacter sp. + 91 ml water), and 1:15 (6 ml Azotobacter sp. + 94 ml water). The results showed that the application of Azotobacter sp. did not significantly affect most growth and yield parameters. Significant effects were only observed on root volume and total soluble solids. The treatment with 100 ml Azotobacter sp. produced the highest root volume (4.00 ml) and total soluble solids (16.20 °Brix) compared to the other treatments. These findings indicate that the application of Azotobacter sp. mainly influenced root development and soluble solid content rather than overall plant growth and yield of Lembah Palu shallots.